Pengaruh Pertumbuhan Ekonomi, Jumlah Penduduk, dan Foreign Direct Investment Terhadap Kualitas Lingkungan - Wibowo, Prasetyo; Kurniawati, Tri (Universitas Negeri Padang, 2024)
The purpose of This study aims to analyze the influence of economic growth, total population, and Foreign Direct Investment on environmental quality. The type of data in this research is quantitative with the data source, namely secondary data, obtained from the Central Statistics Agency of Indonesia. The Secondary data used is the Time Series 2017-2021 and Cross section of districts/cities in West Sumatra province, regarding environmental quality, especially air quality, economic growth, total population , and foreign direct investment. Economic Growth does not have a significant effect on environmental quality variables. Population growth has a significant effect on environmental quality variables. Firen Direct investment does not have a significant effect on the quality of environmental quality.